2022
DOI: 10.3390/aerospace9120826
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Combustion Mode Analysis of a Cavity Based Scramjet

Abstract: Since flame stability is the key to the performance of scramjets, scramjet combustion mode and instability characteristics were investigated by using the POD method based on a cavity-stabilized scramjet. Experiments were developed on a directly connected scramjet model that had an inlet flow of Mach 2.5 with a cavity stabilizer. CH* chemiluminescence, schlieren, and a wall static pressure sensor were employed to observe flow and combustion behavior. Three typical combustion modes were classified by distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Nevertheless, it has been consistently reported that when there was a low global equivalence ratio, the combustion instability was generated in a relatively low-frequency range. [5,9,10,71] However, the interesting point is that the "instability frequency shifting" does not occur by increasing or decreasing the equivalence ratio, as depicted in Figures 26 and 27 and Table 2. Also, Table 3, which arranges the information on the incoming air, fuel injection, and instability frequencies of several experimental studies, provides supporting evidence for this phenomenon.…”
Section: Characteristics Of the Combustion Instabilitymentioning
confidence: 97%
“…Nevertheless, it has been consistently reported that when there was a low global equivalence ratio, the combustion instability was generated in a relatively low-frequency range. [5,9,10,71] However, the interesting point is that the "instability frequency shifting" does not occur by increasing or decreasing the equivalence ratio, as depicted in Figures 26 and 27 and Table 2. Also, Table 3, which arranges the information on the incoming air, fuel injection, and instability frequencies of several experimental studies, provides supporting evidence for this phenomenon.…”
Section: Characteristics Of the Combustion Instabilitymentioning
confidence: 97%
“…Scramjet, as a new type of high-speed propulsion, has become the focus of research. Currently, most of the research is based on liquid fuels such as liquid hydrogen and kerosene [1][2][3][4]. However, the inherent deficiencies of liquid fuel in storage, maintenance, acceleration, stable combustion, rapid response, and technical complexity also bring restrictions to the application of liquid scramjet [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the cavity flame-holding structure has become one of the most common flame stabilization structures in scramjet combustion chambers. In addition to the cavity, baffles and rear steps are also commonly used flame stabilization structures in scramjet combustion chambers [6,7].…”
Section: Introductionmentioning
confidence: 99%